Perancangan Mebel Bermain Anak Guna Meningkatkan Perkembangan Motorik Kasar pada Anak Usia 5-7 Tahun - Christine Bayu Saputra (Intra, 2017)
Activities aren’t only done by mature people, but also children especially those between 5 to 7 years old during their physical and brain growth period are at their peak to reach their optimal function. Teaching children to play and study simultaneously may give the the feeling of euphoria. Also, playing may train their motoric skills, and emotion control. Parent’s role is very crucial toward children’s growth and development owing to the fact that they play a big role in develo ping emotional and social skills as well as increasing their ability to adapt during their pre-school years or after it. The parent also should supervise what the children plays and accompany them during their playing activities.A way to educate children is by giving them a lot of time to play. Children between 5-7 years old are good at playng but not very interested to study in a formal manner.